Phenomenological approach for evaluating problem based learning in architectural education - Abdullah, Fadzidah (IIUM Press, 2013)
This paper explains the step-by-step research approaches adopted while undertaking research thesis titled “An Evaluation of Problem Based Learning in Architectural Education.” This research was designed using the phenomenological approach of case study research. This research is organised around six major topics; the study region, the paradigm and methodology, research method and procedures, analysis of interview data, some ethical considerations and conclusion. This type of interpretative single case study research was selected because it allowed the use of a deduction mode of using the knowledge and information to understand something and form an opinion. Designing research methodology for the thesis requires prior identification of research aim, and objectives. Therefore, careful consideration should be undertaken so that strategies could be designed to achieve the objectives of research. For understanding of this research design, it is important to have context of the research background.